FORMULASI TEPUNG MOCAF, TEPUNG KACANG HIJAU, DAN TEPUNG IKAN SELAR TERHADAP NILAI ENERGI, MUTU KIMIA, DAN MUTU ORGANOLEPTIK COOKIES SEBAGAI PMT ANAK SEKOLAH - Permana, Bayu Daeka; Razak, Maryam; Pudjirahaju, Astutik (Poltekkes Kemenkes Malang, 2023)
The 2018 Basic Health Research reported that 9.2% of school-age children in Indonesia have a thin nutritional status. Furthermore, 16 provinces with a prevalence of underweight nutritional status in school-age children ? 10%. The prevalence of wasting in school-age children is considered a serious health problem if it ranges from 10.0 - 14.0%. Lack of food intake is one of the causes of underweight nutritional status in school children. One of the government's programs to meet the nutritional deficiencies of school-age children is the provision of PMT-AS. Development of PMT-AS cookie products through the use of local foods, namely tubers, nuts and fish with attention to nutrition and organoleptic acceptability. The aim of the study was to analyze the effect of mocaf flour, mung bean flour and selar fish flour formulations on the chemical quality, energy value and organoleptic quality of cookies as PMT-AS. Type Research laboratory experiment research design Completely randomized design (CRD) with the treatment of the proportions of mocaf flour, mung bean flour and selar fish meal. The research used 3 levels of treatment with 3 replications. The results of the research on the formulation of mocaf flour, mung bean flour and selar fish flour had a significant effect on the moisture content, ash content, carbohydrate content, aroma and taste of cookies. However, it had no significant effect on protein content, ash content, fat content, energy content, color and texture. Treatment level (P1) is the best treatment level.